Invited review: Relationship between cattle transport, immunity and respiratory disease. (8th August 2016) - Earley, B.; Buckham Sporer, K.; Gupta, S.
Abstract : The association between transportation and the occurrence of the bovine respiratory disease complex (BRDC) has long been recognised. Many hypotheses regarding this association have been declared through the past decades, and it is agreed upon by most researchers that the multiple stressors that calves experience during transportation result in an overall immunosuppression that allows the respiratory tract to be invaded by numerous opportunistic pathogens. Furthermore, the innate immune cells, neutrophils, may be trapped in a paradox whereby their crucial defence and pathogen-killing activities are counteracted by excessive inflammation and tissue damage that may exacerbate disease, including the BRDC. Neutrophilia in response to glucocorticoids has been attributed to an influx of immature neutrophils newly released from the bone marrow, a decrease in neutrophil margination along endothelial walls, and a decrease in neutrophil apoptosis. Several of these explanations have been confirmed by altered expression of genes and proteins important for neutrophil margination and apoptosis.